Association of Residual Feed Intake With Blood Metabolites and Reproduction in Holstein Cows - Nehme Marinho, Mariana; Santos, José E. P. (Frontiers in Animal Science, 2022)
Objectives were to evaluate the associations between residual dry matter (DM) intake or RFI from 1 to 15 weeks postpartum with concentrations of metabolites in plasma in early lactation and reproduction in Holstein cows. Data from 9 experiments including 851 cows were used in this study. Intake of DM, milk yield, and body weight were evaluated daily, whereas milk composition and body condition were evaluated twice weekly for the first 105 days postpartum. Blood was sampled on the day of calving and again on days 7, 14, and 21 postpartum and analyzed for concentrations of nonesterified fatty acids (FA), β-hydroxybutyrate (BHB), and glucose. Reproduction was evaluated for the first 300 days postpartum. Residual DM intake was calculated as the observed minus the predicted intake, with intake predicted based on a model that accounted for major energy sinks. Cows were ranked and categorized into RFI quartiles, from smallest (Q1) to largest (Q4) RFI. Increasing efficiency (i.e., from Q4 to Q1) resulted in linear decreases in DM intake (Q1 to Q4; 18.4, 20.1, 21.0, and 22.0 kg/day), RFI (-1.86, -0.45, 0.40, and 1.90 kg/day), and median days open (132, 125, 135, 147 d). Conversely, improving efficiency was associated with a linear increase in pregnancy per AI (32.9, 31.0, 31.7, and 25.4%) and quadratic increases in 21-day cycle pregnancy rate (22.5, 21.6, 22.5, and 17.2%) and the proportion of pregnant cows (80.9, 81.6, 83.1, and 73.6%). The estimated net energy for lactation (NEL) content of diets increased linearly with RFI (1.89, 1.77, 1.72, and 1.59 Mcal/kg), resulting in no association between RFI and energy-corrected milk yield or body energy change. Nevertheless, cows with increased feed efficiency had small linear increments in concentrations of blood FA (0.65, 0.61, 0.59, and 0.59 mM) and BHB (0.73, 0.63, 0.63, and 0.64 mM), but no association with glucose. Collectively, the most feed efficient cows ate 3.6 kg/day less DM, produced the same amount of energy-corrected milk, and had improved reproductive performance compared with the least efficient cows, thus suggesting that the underlying mechanisms responsible for improved feed efficiency might also be linked with improvements in reproduction.